Association between serum 25-hydroxyvitamin d and early recurrent ischemic stroke (Annals of Medical Research, 2021)
Aim: Vitamin D deficiency has been reported as a new risk factor for ischemic stroke in recent years. However, the pathophysiological mechanisms between recurrent ischemic stroke and decreased 25-hydroxyvitamin D [25(OH) D] are not clear. The aim of this study is to examine the relationship between initial vitamin D levels and early recurrent stroke in patients presenting with acute ischemic stroke (AIS).Material and Methods: Four hundreds and ten consecutive patients who were followed-up with AIS diagnosis were included in the study. Risk factors for ischemic stroke were questioned and biochemical and cardiac examinations of the patients were performed. Simultaneously, the National Institutes of Health Stroke Scale (NIHSS) was calculated. Patients who had recurrent ischemic stroke obtained retrospectively were from the hospital registry system in last three month. The patients were divided into two groups as those who had recurrent stroke and who did not.Results: A total of 410 patients, 187 of which were female (45.6%) and 223 of which were male (54.4%) with a mean age of 68.12 ± 12.63 (29-99) were included in the study. Early recurrent ischemic stroke was detected in 48 (11.7%) patients in the follow-up. The systolic blood pressure and diastolic blood pressures at the time of first consultation were higher in the recurrent ischemic stroke group compared to the non-recurrent ischemic stroke group (p0.001). Serum total vitamin D and serum parathyroid hormone levels in patients without recurrent stroke were higher as compared with those in patients with recurrent stroke (p0.001). 25(OH) D were significantly associated with stroke recurrence (OR:1.277;Cl 95%, 1.166-1.398; p0.001).Conclusion: Our study showed that decreased serum 25 (OH)D in patients presenting with acute ischemic stroke is associated with recurrent ischemic stroke in the early stage.
Keywords: Ischemic stroke; recurrent stroke; vitamin D